2008
DOI: 10.1159/000119711
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Olfactory System in a Wallaby <i>(Macropus eugenii)</i>

Abstract: We used carbocyanine dye tracing techniques in conjunction with hematoxylin and eosin staining, immunohistochemistry for GAP-43, and tritiated thymidine autoradiography to examine the development of the olfactory pathways in early pouch young tammar wallabies (Macropus eugenii). The overarching aim was to test the hypothesis that the olfactory system of newborn tammars is sufficiently mature at birth to contribute to the guidance of the pouch young to the nipple. Although GAP-43 immunoreactive fibers emerge fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 73 publications
2
21
1
Order By: Relevance
“…However, this sensory system is required only for a simple switch in direction so minimal development may be sufficient. Our behavioural observations disagree with the conclusions of Ashwell et al (2008) and show for the first time that the pouch young of the tammar wallaby is attracted to the odours from the mother's pouch (although our experiments did not assess the specificity of the behavioural response to odour). We conclude that both olfactory systems are capable of receiving odour signals at birth, a function that must be a critical adaptation for the survival of an altricial marsupial neonate such as the tammar for its journey to the pouch.…”
Section: Olfaction Directs the Young To The Pouchcontrasting
confidence: 99%
See 1 more Smart Citation
“…However, this sensory system is required only for a simple switch in direction so minimal development may be sufficient. Our behavioural observations disagree with the conclusions of Ashwell et al (2008) and show for the first time that the pouch young of the tammar wallaby is attracted to the odours from the mother's pouch (although our experiments did not assess the specificity of the behavioural response to odour). We conclude that both olfactory systems are capable of receiving odour signals at birth, a function that must be a critical adaptation for the survival of an altricial marsupial neonate such as the tammar for its journey to the pouch.…”
Section: Olfaction Directs the Young To The Pouchcontrasting
confidence: 99%
“…However, since the mother licks generally over the fur of the lower abdomen (Renfree et al 1989), rather than licking a specific track towards the pouch, this seems unlikely to provide much directional assistance to the young. Ashwell et al (2008) identified neural connections from the olfactory epithelium to the olfactory tubercle and basal forebrain but saw few connections past the olfactory bulb. They concluded that the olfactory system of newborn tammar is not sufficiently developed to play a role in guiding the young to the teat.…”
Section: Olfaction Directs the Young To The Pouchmentioning
confidence: 99%
“…Thus, it turned out that, in newborn marsupials (Macropus eugenii), these pathways are usually too immature to support guidance to the pouch and nipple (Ashwell et al, 2008). Accordingly, at birth, the degree of maturity of these olfactory pathways is not high enough to allow olfaction-mediated behavior in platypus and echidnas, "two modern monotreme lineages that have followed independent evolutionary paths from a less olfaction-specialized ancestor" (Ashwell, 2012).…”
Section: Terminal Nervementioning
confidence: 99%
“…After the remarkable climb to the pouch, other sensory inputs must guide the newborn in finding and attaching to the teat, possibly mediated through the trigeminal pathways and medial medullary reticular formation. Our recent work on olfactory development in this mammal indicate that olfaction is unlikely to play a role in teat-finding behavior [Ashwell et al, 2008]. Although the mechanisms enabling this remarkable independent journey in young marsupials are becoming clearer, discovering their full extent remains an exciting scientific endeavor.…”
Section: Discussionmentioning
confidence: 99%